A novel spray generator for low-energy oil burners. (March 2016) - Etzold, M; Han, Y; Durst, F
Outcomes of development work that resulted in a spray generator which yields spray droplets of small Sauter diameters at very low flow rates through the spray-generating nozzle are reported. This nozzle produces a liquid jet that operates in two modes to switch on or switch off the spray production. To achieve this, a liquid jet impinging on a flat surface is employed. The jet is operated at Ohnesorge–Reynolds numbers that do not yield a spray. The conditions for this state of operation are given. The spray production is, in a second mode of operation, initiated by triggering the Rayleigh instability of this jet so that the impingement on the flat plate occurs in the form of drops. As the drops are initiated, an intermittent spray is produced by the flat surface, that is, each droplet results in a spray leaving the flat surface. This is demonstrated experimentally and measurement results are presented to show that droplets of small Sauter mean diameters are produced in this way. The influence of the jet-generating nozzle diameter on the Sauter diameter is also reported. Comparisons of the droplet-generated sprays are carried out for various other forms of spray generators, keeping the nozzle diameter and the flow rate the same as those for the droplet sprays.